2017
DOI: 10.4168/aair.2017.9.3.257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TiO2Nanoparticles on Inflammasome-Mediated Airway Inflammation and Responsiveness

Abstract: PurposeNanoparticles (NPs) may cause cell and tissue damage, leading to local and systemic inflammatory responses and adverse effects on health due to the inhalation of particulate matter. The inflammasome is a major regulator of inflammation through its activation of pro-caspase-1, which cleaves pro-interleukin-1β (pro-IL-1β) into its mature form and may induce acute and chronic immune responses to NPs. However, little is known about the response of the inflammasome to NP exposure via the airways in asthma. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 40 publications
(50 reference statements)
3
49
0
Order By: Relevance
“…[10][11][12] It has also been shown that TiO 2 NPs increase ROS, inflammation, and apoptosis in the respiratory system. 13 ROS attacks biomolecules such as DNA, proteins, lipids, and carbohydrates, which cause oxidation, methylation, deamination, apoptosis, and, consequently, lead to cell death. 14 Azim et al 7 showed that oral administration of TiO 2 NPs (150 mg/kg/day) for 2 weeks in mice markedly elevated liver enzymes, malondialdehyde (MDA) levels, and gene expressions of NF-κB and Bax in hepatic tissue.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] It has also been shown that TiO 2 NPs increase ROS, inflammation, and apoptosis in the respiratory system. 13 ROS attacks biomolecules such as DNA, proteins, lipids, and carbohydrates, which cause oxidation, methylation, deamination, apoptosis, and, consequently, lead to cell death. 14 Azim et al 7 showed that oral administration of TiO 2 NPs (150 mg/kg/day) for 2 weeks in mice markedly elevated liver enzymes, malondialdehyde (MDA) levels, and gene expressions of NF-κB and Bax in hepatic tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Both COD and TiO2 are phagocytized and NLRP3 inflammasome activating. [20,24,25,38,[41][42][43][44][45][46][47] If they activate also the microglial NLRP3 inflammasome, as is likely, proximal dopaminergic neurons would die. Because the number of microglia approaches the number of neuronal cells of the brain [65] each dopaminergic cell has on the average more than one proximal microglial cell.…”
Section: Discussionmentioning
confidence: 99%
“…In animals inhaling the pigment, TiO2 particles were detected also in the brain. [61] Although the TiO2 particles are phagocytized and activate the NLRP3 inflammasome [20,41,47,79,80] their human pathogenicity is less well established than that of the COD particles. [37,69,81] Nevertheless, treatment of dopaminergic neurons with TiO2 has been shown to increase α-synuclein expression and to cause its aggregation in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in the T H 2 cytokines IL-4, IL-13 and IL-5 were seen, and Mishra et al found elevated Socs3 expression, which is associated with airway inflammation, in TiO 2 exposed mice which was NF-κB-dependent [18]. TiO 2 NPs also increase levels of caspase-1 and activate the NLRP3 inflammasome to generate increased production of pro-inflammatory IL-1β, likely through reactive oxygen species (ROS) production [16]. Genetic susceptibility has also been shown to affect the immune response in the OVA model; Gustafsson et al found differences in TiO 2 -induced inflammation in two susceptible rat strains, with both showing exacerbated IgE production and neutrophilia [19].…”
Section: Enm-induced Asthma Exacerbationsmentioning
confidence: 99%